Current Status on Resource and Production Technologies of Scandium - Osamu TAKEDA; Toru H. OKABE (Journal of MMIJ, 2021)
Scandium possesses unique physical and chemical properties. However, its applications are limited to special/minor fields because of its small production volume and high production cost. While the abundance of scandium in the Earth's crust is not scarce, there are no concentrated ore deposits that are commercially available. Historically, scandium was extracted as a byproduct of uranium and rare earth deposits, and smelted in a small scale. In this review, the characteristics and applications of scandium are briefly introduced. Further, the natural sources of scandium and its current resource developments are discussed. Recent technological developments in the hydrometallurgical process of nickel smelting and the resource potential of scandium from lateritic nickel deposits are also explored. With respect to the production of scandium metal, the development of reduction processes including the electrolytic and the metallothermic reactions is discussed. Finally, the reduction processes for the direct production of aluminum-scandium master alloys are also reviewed.